STRATEGI INOVASI DAN PEMANFAATAN TEKNOLOGI UNTUK DAYA SAING USAHA - Muhammad Iffan Muhammad (EKBIS (Ekonomi & Bisnis), 2020)
This research aims at investigating the impact of innovation strategy and technology utilization on business competitiveness. The quantitative method was implemented by using multiple regression, correlation coefficient, determination coefficient analysis, and hypothesis testing using the classical assumption test. Saturated sampling was also applied as a sampling method by distributing questionnaires to 30 business actors in various distribution shops in Bandung, Indonesia. The results indicated that innovation strategy and use of technology have significant effects on business competitiveness simultaneously. Partially, innovation strategy has a significant effect on business competitiveness, while use of technology has no significant effect on business competitiveness. These results reveal that innovation and technology utilization can provide significant opportunities for business owners to improve, maintain, and develop their business, such as creating trending product designs and utilizing internet promotion channels to various social media. Further research is also needed to understand the strategy innovation and technology that can affect other aspects such as business performance, development, and success.Keywords: Innovation Strategy, Use of Technology, Business Competitiveness